The Homotopy Perturbation Method to Solve a Wave Equation - Gouder, P.M.; Kolli, V.H.; Page, Md. Hanif; Chavaraddi, Krishna B.; Chandaragi, Praveen (Communications in Mathematics and Applications, 2022)
In the paper, we discuss applications of Homotopy Perturbation Method (HPM) related to wave equations subjected to non-local conditions and the method is applied to two test problems in the paper. The method was introduced by J.-H. He (Homotopy perturbation technique, Computer Methods in Applied Mechanics and Engineering 178(3-4) (1999), 257 – 262) and the solutions are matched against exact solutions as in the literature. The results indicate that the HPM produces accurate solutions and faster converging with less computational effort.
Keywords: Homotopy perturbation method; Wave equation; Non-local conditions; Exact solution